Utilization of artificial intelligence in tax audit in Indonesia / Siti Kurnia Rahayu - Rahayu, Siti Kurnia (UiTM Press, 2021)
The purpose of the article is to explain the design of Artificial Intelligence (AI) in the tax audit system which includes the existing status of ICT, the possibility of AI adoption in the Tax Administration System, supporting factors, challenges in implementing AI and the readiness of tax auditors in Directorate General of Taxes (DGT) in implementing AI. The research used a qualitative method through interviews with three key informants. The key informants came from the DGT who designed the Information System at DGT and relevant to the Tax Audit, in Jakarta Indonesia. Apart from key informants, the research also included an analysis of several documents issued by the DGT regarding the Information System at DGT. The data analysis used in this research was inductive analysis. The findings indicate that there are challenges to system development synergy at DGT related to the development process by adopting a private sector work style. DGT is still trying to understand the potential benefits of implementing a system with AI due to the novelty of the system and it has not been tested so that the predictions of benefits are uncertain, as well.